The Peptide/Antibody-Based Surface Decoration of Calcium Phosphate Nanoparticles Carrying siRNA Influences the p65 NF-κB Protein Expression in Inflamed Cells In Vitro - Elena K. Müller; Nataniel Białas; Matthias Epple; Ingrid Hilger (Biomedicines, 2022)
Earlier studies with nanoparticles carrying siRNA were restricted to investigating the inhibition of target-specific protein expression, while almost ignoring effects related to the nanoparticle composition. Here, we demonstrate how the design and surface decoration of nanoparticles impact the p65 nuclear factor-kappa B (NF-κB) protein expression in inflamed leucocytes and endothelial cells in vitro. We prepared silica-coated calcium phosphate nanoparticles carrying encapsulated siRNA against p65 NF-κB and surface-decorated with peptides or antibodies. We show that RGD-decorated nanoparticles are efficient in down-regulating p65 NF-κB protein expression in endothelial cells as a result of an enhanced specific cellular binding and subsequent uptake of nanoparticles. In contrast, nanoparticles decorated with IgG (whether specific or not for CD69) are efficient in down-regulating p65 NF-κB protein expression in T-cells, but not in B-cells. Thus, an optimized nanoparticle decoration with xenogenic IgG may stimulate a specific cellular uptake. In summary, the composition of siRNA-loaded calcium phosphate nanoparticles can either weaken or stimulate p65 NF-κB protein expression in targeted inflamed leucocytes and endothelial cells. In general, unveiling such interactions may be very useful for the future design of anti-p65 siRNA-based nanomedicines for treatment of inflammation-associated diseases.